Efficacy and safety of switching to fixed-dose bictegravir, emtricitabine, and tenofovir alafenamide from boosted protease inhibitor-based regimens in virologically suppressed adults with HIV-1: 48 week results of a randomised, open-label, multicentre, phase 3, non-inferiority trial. Issue 7 (July 2018) - Daar, Eric S; DeJesus, Edwin; Ruane, Peter; Crofoot, Gordon; Oguchi, Godson; Creticos, Catherine; Rockstroh, Jürgen K; Molina, Jean-Michel; Koenig, Ellen; Liu, Ya-Pei; Custodio, Joseph; Andreatta, Kristen; et al.
Summary: Background: Switching from therapy based on a boosted protease inhibitor to bictegravir, emtricitabine, and tenofovir alafenamide could avoid drug interactions and unwanted side-effects in virologically suppressed adults with HIV-1 infection, while maintaining a high barrier to resistance and providing a simplified once-daily, single-tablet regimen. Here, we report 48 week results of a phase 3 study investigating this switch. Methods: In this multicentre, randomised, open-label, active-controlled, non-inferiority, phase 3 trial, adults with HIV-1 infection were enrolled at 121 outpatient centres in ten countries. Eligible participants were aged 18 years or older, had an estimated glomerular filtration rate of 50 mL per min or higher, had been virologically suppressed (plasma HIV-1 RNA <50 copies per mL) for 6 months or more before screening, and were on a regimen consisting of boosted atazanavir or darunavir plus either emtricitabine and tenofovir disoproxil fumarate or abacavir and lamivudine. We randomly assigned participants (1:1), using a computer-generated randomisation sequence, to switch to co-formulated once-daily bictegravir (50 mg), emtricitabine (200 mg), and tenofovir alafenamide (25 mg), herein known as the bictegravir group, or to remain on their baseline boosted protease inhibitor regimen, herein known as the boosted protease inhibitor group, for 48 weeks. Randomisation was stratified by use of tenofovir disoproxil fumarate or abacavir at screening. The primary endpoint was the proportion of participants with plasma HIV-1 RNA of 50 copies per mL or higher at week 48 (by US Food and Drug Administration snapshot algorithm), with a prespecified non-inferiority margin of 4%. Efficacy and safety analyses included all participants who received at least one dose of study drug. This study is ongoing but not actively recruiting patients and is registered with ClinicalTrials.gov, number NCT02603107 . Findings: Between Dec 2, 2015, and July 15, 2016, 578 participants were randomly assigned and 577 were treated (290 in the bictegravir group and 287 in the boosted protease inhibitor group). At week 48, five participants (2%) in the bictegravir group and five (2%) in the boosted protease inhibitor group had plasma HIV-1 RNA of 50 copies per mL or higher (difference 0·0%, 95·002% CI −2·5 to 2·5), thus switching to the bictegravir regimen was non-inferior to continued boosted protease inhibitor therapy. The overall incidence and severity of adverse events was similar between groups, although headache occurred more frequently in the bictegravir group than in the boosted protease inhibitor group. 233 (80%) participants in the bictegravir group and 226 (79%) in the boosted protease inhibitor group had an adverse event. Only two (1%) participants in the bictegravir group and one (<1%) in the boosted protease inhibitor group discontinued treatment because of adverse events. 54 participants (19%) in the bictegravir group had drug-related adverse events compared with six (2%) in the protease inhibitor group. Interpretation: Fixed-dose bictegravir, emtricitabine, and tenofovir alafenamide might be a safe and efficacious alternative to continued boosted protease inhibitor therapy in adults with HIV-1 infection. Funding: Gilead Sciences.